If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Z + 13 = 11 Reorder the terms: 13 + Z = 11 Solving 13 + Z = 11 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + Z = 11 + -13 Combine like terms: 13 + -13 = 0 0 + Z = 11 + -13 Z = 11 + -13 Combine like terms: 11 + -13 = -2 Z = -2 Simplifying Z = -2
| X+11-9= | | 1.4-4.5q=-(4q-1) | | 0-6y=11 | | q=2m+2x | | -12w=-138 | | 2x+3x-16+x+x+8=360 | | 3(x-5)+8-x= | | -x^2+7x=5 | | 177=6X-46 | | 2log(x-5)=0 | | 4+9x-11=3(3x-5) | | 5y^2-7y-6= | | 8(1-m)+2(4-m)=3(6-3m)-5(m-2) | | 3x-6x-34=0 | | -x(2)+7x=5 | | 8x-10=-3y+2 | | 1x+15=2x+10 | | 0=10000-10x | | 6x+4-5x-20=40 | | 9k+36k+35=0 | | x+3(4)=18 | | 2x-y+z=0 | | 72x*(x^5+y^2)= | | x^3+5x^2+24x=0 | | 1x+15=3x | | 72x(5x+2y)= | | 100x+50y+20z=3150 | | 8.2=y-3.9 | | 7(x-5)=3(4-x) | | 3+4=121 | | 26.5=n+2.08 | | x=11+6y |